Role of Retinol-binding Protein 4 as an Early Biomarker for Diabetic Nephropathy in Type 2 Diabetic Patients (Medico Legal Update, 2021)
Assess the relationship and diagnostic performance of retinol-binding protein 4 (RBP-4) as a biomarker ofdiabetic nephropathy (DN) at different levels of albuminuria (normo-, micro- and macro-albuminuria). Acase-control study, that involved 185 participants, 47 were healthy control, and 138 diabetic patients (46were normoalbuminuric patients [NA], 48 patients were microalbuminuria [MiA], and 44 patients weremacroalbuminuria [MaA]). All diabetic patients were treated with antidiabetic medication (metformin and/or oral sulfonylureas), all the participants were interviewed by the researcher, and full medical (history ofliver, kidney, lung, and other diseases), and sociodemographic data taken from them and recorded in thequestionnaire. In the present study, RBP-4 was 14.08±1.82 ng/ml in the control group, 15.98±3.74 ng/mlin the normoalbuminuria (NA) group, 30.38±6.02 ng/ml in the micro-albuminuria (MiA), and 41.01±5.78ng/ml for macro-albuminuria (MaA), there was a significant difference between all their groups comparedto control (p-value